Epidemiologia molecular da hanseníase: sorologia anti PGL-I e PCR em swab nasal de pacientes com hanseníase e contatos domiciliares - Araújo, Sérgio (2012)
Leprosy is one of the oldest and most instigating diseases to affect humans. Molecular and immunological tools are evaluated in epidemiological studies; however, the results present controversies mainly due to disease complexity and methodologies. This study describes the application of anti PGL-I serology and nasal swab DNA detection to characterize Mycobacterium leprae molecular epidemiology in patients and household contacts of leprosy patients. Among leprosy patients the positivity to the anti PGL-I ELISA and the PCR for the detection of M. leprae DNA in nasal swabs are inversely associated to the lepromin test and arte directly associated to the bacillary index and the clinical forms in the disease spectrum, increasing towards baciliferous forms. The overall positivity percentages were 63.3% for the anti PGL-I ELISA and 34.2% for the PCR for the detection ofM. leprae DNA in nasal swabs. Among household contacts of leprosy patients the overall percentages for the anti PGL-I ELISA and for the PCR for the detection of M. leprae DNA in nasal swabs were 13.3% e 4.7% respectively. Among leprosy patients, assays positivity is associated with the clinical presentation of the disease, increasing towards bacilliferous subtypes. Positive results in contacts represent healthy carriers and subclinical infection and these individuals can participate in transmission and spread of M. leprae in the community, even though they may not develop the disease. In endemic regions, contact monitoring is imperative in leprosy control for early case detection and chemoprophylaxis must be applied as prevention to disease development and disruption of transmission.